2014
DOI: 10.1098/rsbl.2014.0348
|View full text |Cite
|
Sign up to set email alerts
|

Different on the inside: extreme swimbladder sexual dimorphism in the South Asian torrent minnows

Abstract: The swimbladder plays an important role in buoyancy regulation but is typically reduced or even absent in benthic freshwater fishes that inhabit fast flowing water. Here, we document, for the first time, a remarkable example of swimbladder sexual dimorphism in the highly rheophilic South Asian torrent minnows (Psilorhynchus). The male swimbladder is not only much larger than that of the female (up to five times the diameter and up to 98 times the volume in some cases), but is also structurally more complex, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…). Drumming muscles are rare in cypriniforms, but have been found in Sundadanio (Conway and Britz, ) and Psilorhynchus (Conway et al, ), although the drumming apparatus in the latter two is quite different from that of D. dracula and does not include a drumming cartilage. In addition, male D. dracula have several areas of their skeleton affected by hyperossification, which often accompanies miniaturization in vertebrates, as also pointed out by Hanken ().…”
Section: Discussionmentioning
confidence: 99%
“…). Drumming muscles are rare in cypriniforms, but have been found in Sundadanio (Conway and Britz, ) and Psilorhynchus (Conway et al, ), although the drumming apparatus in the latter two is quite different from that of D. dracula and does not include a drumming cartilage. In addition, male D. dracula have several areas of their skeleton affected by hyperossification, which often accompanies miniaturization in vertebrates, as also pointed out by Hanken ().…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sexual dimorphisms in the swim bladders of South Asian torrent minnows (Psilorhynchidae; Conway, Britz, & Siegel, ), Atlantic croakers (Sciaenidae; Hill, Fine, & Musick, ), oyster toadfish (Batrachoididae; Fine et al, ) along with several species of cusk eels (Ophidiidae) with implications for sound production (Courtenay, ; Kéver et al, ; Rose, ). While Bass and Marchaterre () reported overall size differences in gross dissections of the swim bladders of plainfin midshipman across sexual phenotypes, no study has yet provided evidence for functional differences in swim bladders between the sexes, nor between alternative sexual phenotypes of a given sex as it relates to sound reception.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sexual dimorphisms in the swim bladders of South Asian torrent minnows (Psilorhynchidae;Conway, Britz, & Siegel, 2014), Atlantic croakers (Sciaenidae;Hill, Fine, & Musick, 1987), oyster toadfish (Batrachoididae;Fine et al, 1990) along withFIG URE 4 Representative computerized tomography (CT) scans of a female, type I and II male that show differences in swim bladder shape and relative proximity of the swim bladder to the inner ear otoliths of Porichthys notatus. The largest otoliths reside in saccule (SO), the main end organ of hearing in this species, while ventro-caudal to the saccular otoliths are the otoliths of lagena (LO), also a putative midshipman auditory end organ, and then medial-anterior to the saccular otoliths are the otoliths of the utricle (UO), a putative vestibular and auditory end organ.…”
mentioning
confidence: 99%
“…In non-ophidiiform teleosts, sexual dimorphism in the sound production apparatus seems to be commonly related to the size of sonic muscles and swimbladder (Kratochvil, 1980;Fine et al, 1990;Brantley et al, 1993) or the absence or presence of sonic muscles (Hill et al, 1987;Tellechea and Norbis, 2012). However, the recent work of Conway et al (Conway et al, 2014) highlighted extreme (shape and size) internal dimorphisms in some minnows, which suggest that pronounced intersexual differences may have been missed, even in well-studied groups. In the past, sex-related differences in the soundproduction apparatus (and sounds) of carapids may have been overlooked because they are inconspicuous, especially when compared with the sexual dimorphism observed in the sister family Ophidiidae (Rose, 1961;Courtenay, 1971;Kéver et al, 2012).…”
Section: Introductionmentioning
confidence: 98%